An overview of virtual machine live migration techniques - Artan Mazrekaj; Shkelzen Nuza; Mimoza Zatriqi; Vlera Alimehaj (Institute of Advanced Engineering and Science, 2019)
In a cloud computing the live migration of virtual machines shows a process of moving a running virtual machine from source physical machine to the destination, considering the CPU, memory, network, and storage states. Various performance metrics are tackled such as, downtime, total migration time, performance degradation, and amount of migrated data, which are affected when a virtual machine is migrated. This paper presents an overview and understanding of virtual machine live migration techniques, of the different works in literature that consider this issue, which might impact the work of professionals and researchers to further explore the challenges and provide optimal solutions.